Pengaruh Brand Image, Harga, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Smartphone Merek Oppo Pada Toko Handphone Mbahjo Cell Dibandar Kota Kediri - Cindy Wahyu Valentine; Edi Murdiyanto; Zaenul Muttaqien (Journal of Management and Social Sciences, 2023)
This study discusses the influence of brand image, price, and service quality on the purchase decision of OPPO brand smartphones at the MbahJo Cell mobile phone store in Kediri city. This study aims to determine and explain the results of the influence of brand image, price, and service quality on the purchase decision of OPPO brand smartphones at the MbahJo Cell mobile phone store in Kediri City. This type of research uses associative research using quantitative methods. The sample in this study was only on consumers who were making a purchase decision on OPPO smartphones at the MbahJo Cell mobile phone store as many as 102 consumers. The sampling technique uses Non-Probability Sampling with the Accidental Sampling method. Data collection techniques use questionnaires that have been tested for validity and reliability. The data analysis technique used is a classical assumption, multiple linear regression. The result of this study is that there is a significant influence of brand image on purchasing decisions with a value of Sig. 0.000 < 0.05. There is a significant influence of price on purchasing decisions with values of Sig. 0.037 < 0.05. There is a significant influence of service quality on purchasing decisions with a value of Sig 0.000 < 0.05. There is a simultaneous influence of brand image, price, and service quality on purchasing decisions with a Sig. value of 0.000 < 0.05.